Prediction of Complete Necrosis of Hepatocellular Carcinoma Treated with Transarterial Chemoembolization Prior to Liver Transplantation - Kim, Sue Jin (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Society of Pancreatobiliary Diseases, 2009)
BACKGROUND/AIMS: Compact lipiodol uptake without enhancement on multiphasic helical computed tomography (CT) has been suggested as a radiologic response criterion in hepatocellular carcinoma (HCC) patients treated with transarterial chemoembolization (TACE) and subsequent partial hepatectomy. However, its usefulness has not been fully investigated in the explanted liver. METHODS: Between 1998 and 2007, 81 patients with HCC underwent 1-9 sessions of TACE followed by liver transplantation (LT). Thirty-nine tumors in 29 patients showed a radiologic response on CT performed prior to LT. The radiologic response criteria and the duration of the response were evaluated to predict total necrosis in the explanted liver. RESULTS: Among the 39 tumors, 34 nodules (87.2%) exhibited total pathological necrosis. While 13 out of 16 tumors (81.3%) with a radiologic response for 6 months or less were completely necrotic, 21 out of 23 tumors (91.3%) with a radiologic response of longer than 6 months showed total necrosis. CONCLUSIONS: Our results suggested that the radiologic response criteria based on serial CT images might be useful for predicting total necrosis of TACE-pretreated HCC in LT.